In vitro Antioxidant Evaluation of Wood Vinegars from Carbonization of Wood and Bamboo - Yongyuth Theapparat (Science Faculty of Chiang Mai University, 2019)
Six carbonizing wood vinegars consisting of Dendrocalamus asper (Bamboo), Hevea brasiliensis (Rubberwood), Jatropha curcas (Jatropa), Leucaena leucocephala (White popinac), Eucalyptus camaldulensis (Eucalyptus), and Azadirachta indica (Neem) were assessed for their antioxidant activity by measuring their capability for scavenging1,1-diphenyl-2-picrylhydrazyl (DPPH) radical, hydroxyl free radical, superoxide anion radical, as well as ferric reducing power, and anti-lipid peroxidation capacity. Total phenol content was also evaluated using Folin-Ciocalteu assay expressed as gallic acid equivalent. All wood vinegars exhibited better DPPH radical scavenging capacity than positive controls, ascorbic acid and BHT. The wood vinegars from bamboo and rubberwood exhibited good antioxidant capacity in all assays tested comparable or better than a positive control, BHT. In addition the DPPH radical scavenging capacity, hydroxyl free radical scavenging capacity, ferric reducing power and anti-lipid peroxidation capacity showed good correlations with their total phenolic contents with correlation, R2 values ranging from 0.92-0.99. The results of the present study suggested that wood vinegars have high potential to be useful as beneficial natural antioxidant compound in feed additives and veterinary medicine. In addition the total phenol content in wood and bamboo vinegars have a potential quality index to evaluate the scavenging ability of DPPH radical, hydroxyl free radical capacity, ferric reducing power and anti-lipid peroxidation.